Data on chemical activation of Wnt/β-catenin during axolotl limb regeneration - Sabina Wischin; Cristina Castañeda-Patlán; Martha Robles-Flores; Jesús Chimal-Monroy (Data in Brief, 2017)
Limb amputation in axolotls was performed to obtain data demonstrating that a chemical agonist of Wnt (int-related protein)/β-catenin signalling can have a role in axolotl limb regeneration (Wischin et al., 2017) [1]. The data revealed that active β-catenin protein was present during limb regeneration in some Leydig cells in the epithelium; after the chemical treatment, it was observed in more Leydig cells. In addition, the chemical agonist of Wnt generated distinct limb malformation.